Die Kindheidsevangelie van Tomas – historiese allegorie of mite in die vorm van "n biografiese diskursiewe evangelie? - Aarde, Andries van (HTS teologiese studies, 2005)
The Infancy Gospel of Thomas – historical allegory or myth in the format of a biographical discursive gospel?The article argues that the Greek version of the Infancy Gospel of Thomas in Codex Sinaiticus (Gr 453) represents the genre of a discursive-biographical gospel type and as a result, the narrative and argumentative structure of this infancy gospel is of importance. So too is the phenomenon that the narrative argument of the Infancy Gospel of Thomas is cast in the form of the ancient god-child myth. This article theorizes about myth by exploring it as folklorist art and its function as model for behaviour. In the Infancy Gospel of Thomas as a myth of a child-god the child Jesus acts as if he were an adult. This adult-like behaviour of the child Jesus is not interpreted in an allegorical way. Rather, as myth, the message is interpreted in a tautegoric manner and explained in a social scientific way.